Information technology, improved access and use of prescription drugs - Böckerman, Petri (Oxford University Press, 2025)
We estimate the effects of health information technology designed to improve access to medication while limiting overuse through easier prescription renewal and improved information provision. We focus on benzodiazepines, a commonly prescribed class of mental health and insomnia medications, which are highly effective but potentially addictive. We study the staggered rollout of a nationwide electronic prescribing system over four years in Finland and use population-wide, individual-level administrative data sets. We find that e-prescribing increases average benzodiazepine use due to increased prescription renewals. The increase is most pronounced for younger patients. E-prescribing can improve the health of elderly patients and may help to balance the access-overuse trade-off. Without additional monitoring for addiction in place, it may, however, also have unintended health consequences for younger patients, who are more likely to develop mental and behavioral health disorders.